Respuesta :
Answer:
23 rungs
Step-by-step explanation:
Let the number of rungs on the ladder be h and make the necessary adjustments based on this
Given that she is on the middle rung of a ladder this is equivalent to
= (h + 1)/2
She climbed up three rungs
= (h + 1)/2 + 3
moved down five rungs
= (h + 1)/2 + 3 - 5
and then climbed up 7 rungs
= (h + 1)/2 + 3 - 5 + 7
Then she climbed up the remaining 6 rungs to the top of the ladder
(h + 1)/2 + 3 - 5 + 7 + 6 = h
(h + 1)/2 + 11 = h
h + 1 + 22 = 2h
2h - h = 23
h = 23